Osteoclasts control osteoblast chemotaxis via PDGF-BB/PDGF receptor beta signaling. - Maria Arantzazu Sanchez-Fernandez; Anne Gallois; Thilo Riedl; Pierre Jurdic; Bernard Hoflack (PLoS ONE, 2008)
Bone remodeling relies on the tightly regulated interplay between bone forming osteoblasts and bone digesting osteoclasts. Several studies have now described the molecular mechanisms by which osteoblasts control osteoclastogenesis and bone degradation. It is currently unclear whether osteoclasts can influence bone rebuilding.Using in vitro cell systems, we show here that mature osteoclasts, but not their precursors, secrete chemotactic factors recognized by both mature osteoblasts and their precursors. Several growth factors whose expression is upregulated during osteoclastogenesis were identified by DNA microarrays as candidates mediating osteoblast chemotaxis. Our subsequent functional analyses demonstrate that mature osteoclasts, whose platelet-derived growth factor bb (PDGF-bb) expression is reduced by siRNAs, exhibit a reduced capability of attracting osteoblasts. Conversely, osteoblasts whose platelet-derived growth factor receptor beta (PDGFR-beta) expression is reduced by siRNAs exhibit a lower capability of responding to chemotactic factors secreted by osteoclasts.We conclude that, in vitro mature osteoclasts control osteoblast chemotaxis via PDGF-bb/PDGFR-beta signaling. This may provide one key mechanism by which osteoclasts control bone formation in vivo.